1981
DOI: 10.1128/aac.20.2.239
|View full text |Cite
|
Sign up to set email alerts
|

Comparative in vitro synergistic activity of new beta-lactam antimicrobial agents and amikacin against Pseudomonas aeruginosa and Serratia marcescens

Abstract: The in vitro synergistic activities of moxalactam, cefoperazone, or cefotaxime in combination with amikacin or piperacillin were compared against aminoglycoside-susceptible and aminoglycoside-resistant isolates of Pseudomonas aeruginosa and Serratia marcescens by the checkerboard agar dilution method. All antimicrobial combinations demonstrated some synergy, and no antagonism was observed. Moxalactam plus amikacin and piperacillin plus amikacin were most frequently synergistic (two-thirds of the isolates inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0
1

Year Published

1982
1982
1988
1988

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(26 citation statements)
references
References 21 publications
2
23
0
1
Order By: Relevance
“…There have been previous studies purporting to show synergistic killing by combinations of AMGs and betalactams for strains which were resistant to one or the other agent of the combination or, in some cases, to both agents when used alone (19). Our data indicate that synergistic killing was more likely when the isolate was susceptible to one or both of the agents and was less likely when it was resistant to both antimicrobial agents.…”
Section: Resultssupporting
confidence: 48%
See 1 more Smart Citation
“…There have been previous studies purporting to show synergistic killing by combinations of AMGs and betalactams for strains which were resistant to one or the other agent of the combination or, in some cases, to both agents when used alone (19). Our data indicate that synergistic killing was more likely when the isolate was susceptible to one or both of the agents and was less likely when it was resistant to both antimicrobial agents.…”
Section: Resultssupporting
confidence: 48%
“…Moreover, these antimicrobial agents have been found to be especially useful when combined with an aminoglycoside (AMG) in the treatmnent of severe infections with gram-negative bacilli (1,2), perhaps reflecting their in vitro synergistic activity (10,11,13,15,16,19,24).…”
mentioning
confidence: 99%
“…Similarly, comparison of beta-lactam-aminoglycoside interactions against P. aeruginosa by checkerboard MIC testing and 6-or 24-h time-kill curves results in concordance rates of <50% between any pair of methods (35,36). On the other hand, several studies examining small numbers of strains have suggested rough correlations between results obtained by different methods (110,191). Klastersky et al (101) found agreement between time-kill and MBC checkerboard assessment of cefazolin-amikacin interactions for 60% (13 of 20) of Klebsiella isolates.…”
Section: Correlation Of Results By Various Methodsmentioning
confidence: 99%
“…Beta-lactam combinations may also exhibit antagonistic effects (2,75). Unlike beta-lactam-aminoglycoside combinations (with which antagonism has been reported but appears to be distinctly uncommon), antagonism of one beta-lactam by another is not rare (59,95,109,110,138,179). For example, Neu and Fu (138) detected antagonism between azlocillin and cefazolin against 16% of gram-negative bacilli tested.…”
Section: Enzyme Inhibitorsmentioning
confidence: 99%
“…Assuming that an MIC of 32 ,ug/ml to be the upper limit of susceptibility, only 16% of these organisms were resistant. As has been the experience in other studies, many (40%) of our P. aeruginosa strains were resistant (2,(6)(7)(8)(9)21 (2,6,7,9), Streptococcus pyogenes (2,6,7,9,20), and Listeria monocytogenes (7). The resistance of moxalactam to hydrolysis by ,-lactamase elaborated by Staphylococcus aureus (4) and the infrequent production of this enzyme type by other gram-positive organisms argue against a ,-lactamase enzymatic mechanism as an explanation of relative moxalactam insusceptibility in this population.…”
Section: Resultsmentioning
confidence: 74%